Correction: Factors affecting Dupont's lark distribution and range regression in Spain. - Alexander García Antón; Vicente Garza; Jorge Hernández Justribó; Juan Traba (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0211549.].